2009
DOI: 10.1007/s00216-009-2835-4
|View full text |Cite
|
Sign up to set email alerts
|

Calibration possibilities and modifier use in ETV ICP OES determination of trace and minor elements in plant materials

Abstract: The possibilities for universal calibration based on multi-element aqueous standard solutions and graphite laboratory reference materials (graphite standards) for the electrothermal vaporization inductively coupled plasma optical emission spectrometric (ETV ICP OES) determination of Al, B, Ba, Cd, Co, Cr, Cu, Fe, Mn, Ni, P, Pb, S, Sr, Ti, V, and Zn in plant materials were investigated. A commercially available state-of-the-art ETV device was coupled with an Echelle ICP spectrometer equipped with a charge-injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…In this way, the organic matter was eliminated and matrix effects reduced as observed by the similarity of the analyte signal profiles in the presence and absence of sample. Additionally, as observed by Detcheva et al 29 and Barth et al, 24 halogencontaining modifiers (such as CCl 2 F 2 ) buffer differences related with the analyte chemical form, which may be different in samples and calibration solution. Consequently, the analyte present in the solid sample and in the dried solution has a quite similar vaporization behavior, as observed in the present work.…”
Section: Resultsmentioning
confidence: 83%
“…In this way, the organic matter was eliminated and matrix effects reduced as observed by the similarity of the analyte signal profiles in the presence and absence of sample. Additionally, as observed by Detcheva et al 29 and Barth et al, 24 halogencontaining modifiers (such as CCl 2 F 2 ) buffer differences related with the analyte chemical form, which may be different in samples and calibration solution. Consequently, the analyte present in the solid sample and in the dried solution has a quite similar vaporization behavior, as observed in the present work.…”
Section: Resultsmentioning
confidence: 83%
“…The carbonization procedure described in Detcheva et al. 8 and external calibration based on cellulose were used for determining low concentrations of Pt, Pd, and Rh in Brassica napus using ETV-ICP-AES. 10…”
Section: Introductionmentioning
confidence: 99%
“…The combination of ICP-AES with electrothermal vaporization (ETV) makes it possible to apply solid sampling in analysis of plants. Detcheva et al 8 showed the possibilities of ETV-ICP-AES for determining the 12 elements in different leaf certified reference materials (CRM) after previous carbonization of the samples. Calibration based on multielement aqueous standard solutions or graphite reference materials were used.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct analysis, with little or without prior chemical treatment, is desirable because of the simplicity of the analytical procedure and reduction of the risk of contamination and analyte loss. Combination of electrothermal atomization and vaporization with the above methods allows analysis of solid biological samples, but different behavior of the analytes during evaporation, poor reproducibility, and calibration requirements make it difficult to use these methods for routine multielemental analysis [1319]. Using laser ablation ICP-MS [20, 21], X-ray fluorescence spectrometry [22, 23] and neutron activation analysis (NAA) [24] for direct analysis of solid biological samples are also complicated by lack of certified reference materials (CRMs) with different biological matrices.…”
Section: Introductionmentioning
confidence: 99%